2007
DOI: 10.1158/1541-7786.mcr-07-0010
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Cyclooxygenase-2 Inhibits Metastasis and Delays Tumor Onset of Poorly Differentiated Metastatic Breast Cancer Cells

Abstract: Cyclooxygenases (COX) are rate-limiting enzymes involved in the conversion of PLA 2 -mobilized arachidonic acid into prostaglandins and thromboxanes. COX-2 is a key mediator of inflammation during both physiologic and pathologic responses to endogenous stimuli and infectious agents. Its overexpression has been detected in different cancers, including that of the breast. Using RNA interference, we have reduced the expression of COX-2 in the highly malignant breast cancer cell line MDA-MB-231 below detectable le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 32 publications
8
65
0
Order By: Relevance
“…High PGE 2 levels are observed in many human breast cancers [5], and COX-2 is closely involved in tumor growth, invasion, and metastasis [14]. Consequently, COX-2 is considered a target for breast cancer therapy and chemoprevention strategies.…”
Section: Inhibition Of Cox-2 Protein Expression By Starfish Polysacchmentioning
confidence: 99%
See 1 more Smart Citation
“…High PGE 2 levels are observed in many human breast cancers [5], and COX-2 is closely involved in tumor growth, invasion, and metastasis [14]. Consequently, COX-2 is considered a target for breast cancer therapy and chemoprevention strategies.…”
Section: Inhibition Of Cox-2 Protein Expression By Starfish Polysacchmentioning
confidence: 99%
“…Masferrer et al (2000) and Kundu and Fulton (2002) demonstrated antiangiogenic, antimetastatic, and antitumor activities of COX-2 inhibitors [7,15]. Another study found that silencing COX-2 in MDA-MB-231 cells led to the induction of antiangiogenic gene expression and the reduction of prometastatic transcription [14]. In the present research, starfish polysaccharide effectively inhibited TPA-induced COX-2 expression in MDA-MB-231 breast cancer cells in a dose-dependent manner (Fig.…”
Section: Inhibition Of Cox-2 Protein Expression By Starfish Polysacchmentioning
confidence: 99%
“…Indeed, elevated levels of COX-2 in breast cancers are associated with a poor prognosis and ductal carcinoma in situ recurrence (18). Studies show that COX-2 is involved in breast cancer cell proliferation, migration, and invasion (19,21), and when the enzyme is knocked out, mice develop fewer mammary tumors (22), whereas overexpression of COX-2 in the mammary gland induces tumors (23). Moreover, although sometimes contradictory, epidemiological evidence suggests a correlation of intake of non-steroidal anti-inflammatory drugs (inhibitors of the COX enzymes) with decreased risk of breast cancer (24).…”
mentioning
confidence: 99%
“…In contrast to fetal hepatocytes, which expressed COX-2 in response to proinflammatory stimuli, adult hepatocytes failed to express COX-2 regardless of the type of challenge (19). However, overexpression of COX-2 was commonly related to different types of carcinomas, including hepatocellular carcinoma (20)(21)(22)(23). It was evident that COX-2 could enhance hepatocellular carcinoma invasiveness by promoting hepatocellular carcinoma proliferation and tumor angiogenesis (24,25).…”
mentioning
confidence: 99%
“…Recent studies showed that downregulation of COX-2 expression via RNAi inhibited tumor cell proliferation and colony formation in vitro in different types of cancer cells (2,23,24). COX-2 silencing abolished the metastatic potential of the highly malignant breast cancer cells (21). Therefore, in this study we constructed an adenoviral vector with newly developed coexpression system to express shRNA against COX-2 and the therapeutic gene TRAIL and explored its antitumor potential in experimental hepatocellular carcinoma.…”
mentioning
confidence: 99%